A Szenci Molnár Albert-kutatás jelenlegi állása: Eredmények és feladatok - P. Vásárhelyi, Judit (Studia Litteraria, 2026)
The author is pleased to conclude that over the past fifty years, research on Albert Molnár Szenci’s oeuvre has made considerable progress. Almost all his works are now available in facsimile or digital editions. Thus, his oeuvre can be objectively analysed in its entirety and in detail, free from excessive bias or reservations. The study lists Molnár’s printed and manuscript works and translations that have not survived, but whose existence can be reasonably proven. In addition to the search for these, the aim of future research is to produce a modern critical edition of his letters and occasional Latin poems, to process and publish his collection of commonplaces, to reconstruct his library, to prepare a bibliography of the Genevan Psalms in Hungarian, and to write his monography.